The Bandung Spirit: Nation State and Democracy - Cornelis Lay (Journal of Indonesian Social Sciences and Humanities, 2016)
This article aims to show the relevance of the Bandung Asia Africa Conference in 1955 to the current debate on democracy. It argues that the Bandung Asian-African Conference was the second massive but wellcoordinated democratic movement on a global scale. It has paved the way for the production of new political space globally as well as for individual nations -- space that is more democratic in nature, where people can claim and exercise their citizenship rights. Re?ecting on Soekarnos speech at the opening of the Asia Africa Conference, this article argues that there is an urgent need for a deeper involvement of political and social forces of the Global South to put themselves as the front liners in defning and making use of democracy, instead of leaving it to be dictated by Neo-liberal lines of thinking. This is so because Indonesian experience during the last 15 years or so has clearly demonstrated the very limits of liberal democracy. This article further argues the need to build a collaborative e?ort amongst scholars of the Southern Hemisphere to challenge the superiority of liberal ideas and practices of democracy.